(untitled) (Comprehensive Journal of Science, 2025)
This study highlights the role of good governance in promoting green management and corporate social responsibility (CSR) as key mechanisms for achieving sustainable development. Using a theoretical analytical approach based on relevant literature and previous studies, the research finds that governance provides a framework ensuring transparency and accountability while supporting environmentally and socially responsible practices. The study concludes that integrating governance with green management and CSR enhances institutional performance and contributes to achieving a balance among the economic, social, and environmental dimensions of sustainable development.